2014
DOI: 10.1902/jop.2013.130008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glycemic Control on Self‐Perceived Oral Health, Periodontal Parameters, and Alveolar Bone Loss Among Patients With Prediabetes

Abstract: Self-perceived oral health, severity of periodontal parameters, and MBL are worse in patients with prediabetes than controls. Glycemic control significantly reduces the severity of these parameters as well as the state of prediabetes in affected individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 32 publications
1
50
0
1
Order By: Relevance
“…It is well known that periodontal inflammatory conditions are worse in immunocompromised individuals, cigarette smokers, and individuals chewing smokeless tobacco products [15,17,[22][23][24][25][26][27][28]. Moreover, it has also been reported that the outcomes of periodontal surgical interventions are compromised in tobacco smokers [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that periodontal inflammatory conditions are worse in immunocompromised individuals, cigarette smokers, and individuals chewing smokeless tobacco products [15,17,[22][23][24][25][26][27][28]. Moreover, it has also been reported that the outcomes of periodontal surgical interventions are compromised in tobacco smokers [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that periodontal infl ammatory conditions are worse in immunocompromised individuals and individuals chewing smokeless tobacco products [10,12,[14][15][16][17][18][19][20][21] It is therefore hypothesized that the outcomes of SRP (regardless of using essential-oil-based mouthwash Duration of smoking habit (in years) 10.6 ± 3.5 10.5 ± 2.8…”
Section: Discussionmentioning
confidence: 99%
“…UWS was collected at early morning hours as described elsewhere [13]. Briefl y, all participants were comfortably seated on a chair and requested to spit (without swallowing) into a funnel connected to a gauged measuring cylinder for fi ve continuous minutes.…”
Section: Collection Of Unstimulated Whole Saliva Samplesmentioning
confidence: 99%